NILAI-NILAI ANTIKORUPSI DALAM PENDIDIKAN ISLAM: Tinjauan Normatif Aspek Kurikulum Pendidikan Agama Islam Terhadap Pendidikan Antikorupsi - Bueti, A. (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
In this study to find out how the concept of educators and students and the purpose of this study to find out how the concept of educators and students of Abuddin Nata and Zakiah Daradjat's thoughts. This study is library research. The primary data source is the book of Islamic Education Science and Islamic Perspectives on Learning Strategies by Abuddin Nata, the book of Islamic Education Science and Special Methods of Islamic Religious Teaching by Zakiah Daradjat. While the secondary is books that are relevant to this study. The data collection technique uses documentation and the analysis used is content analysis. The results of this study provide the conclusion that first, the concept of educators of Abuddin Nata's thoughts is someone who is knowledgeable and has broad insight, has skills, experience, has a noble personality, understands what is written and implied, becomes an example and model for students. Second, the concept of educators of Zakiah Daradjat's thoughts is a professional educator who is able to foster all the abilities and good attitudes of students, as a teacher who guides and fosters the development of knowledge, attitudes and skills. Third, the concept of learners according to Abuddin Nata is someone who not only involves children but also adults, while students are only intended for individuals who are children, learners are also partners in teaching and learning activities. And fourth, the concept of learners according to Zakiah Daradjat is a unique individual who has potential and experiences a development process, learners are also subjects and objects in teaching and learning interactions, learners receive lessons and guidance from educators